Lanthanide Metal-Organic Frameworks for Advanced Energy Systems - Manning, Gearóid (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2026)
Lanthanide-based metal-organic frameworks (Ln-MOFs) combine accessible Ce³⁺/Ce⁴⁺ and Eu³⁺/Eu²⁺ redox couples, aqueous and pH stability, and the structural tunability of reticular chemistry, yet remain underexploited as redox catalysts for solar-to-fuel applications. This thesis investigates the use of novel Ln-MOFs and their derivatives as electrocatalysts and photocatalysts for artificial photosynthesis, with a focus on the role of linker design in shaping catalytic performance of Ln-MOFs under both electrocatalytic and photocatalytic conditions. In the first part of the thesis, a series of structural related Ce(III)-MOFs constructed from tritopic aromatic linkers is shown to are shown act pre-catalysts for cerium(IV) oxide species under the harsh acidic conditions relevant to proton-exchange membrane electrolysers. Pyrolysis of the same Ce-MOF series yields CeO₂-carbon composites that further improved oxygen evolution activity. Pyrolysis of the thiophene-containing Ce-MOF additionally produces a Ce₂S₃ phase via in-situ carbothermic sulfurisation, to the author's knowledge the first lanthanide(III) sulfide phase synthesised from a MOF precursor. In the second part of the thesis, an acetylene-extended Ru(II) polypyridyl metalloligand is incorporated as a photosensitising linker in a novel isostructural series of two-dimensional Ln-MOFs spanning Ce to Er, a rare example of a lanthanide coordination series structurally uninterrupted by the gadolinium break. Photophysical studies reveal systematic emission shifts tracking Ln(III) Lewis acidity and an extended Ru(II) ³MLCT excited-state lifetime. The Ce and Eu analogues are subsequently demonstrated as photocatalysts for water oxidation, hydrogen evolution, and (for the Eu analogue) selective CO₂ reduction to formate. Beyond demonstrating the efficacy of redox active Ln-MOF catalysts (utilising Ce³⁺/Ce⁴⁺ and Eu³⁺/Eu²⁺ redox couples), the results of this thesis reinforce the importance of linker choice in the design of Ln-MOF catalysts. The choice of tritopic linker was shown to influence catalytic activity in the Ce-MOF series and could also determine the phases formed upon pyrolysis. The Ru(II) polypyridyl linker was shown to both photosensitise the LnRu-MOFs and, through its alkynyl bridge, is proposed to facilitate interfacial electron transfer to the Ln SBUs.
APPROVED
Keywords: Metal-Organic Frameworks; Lanthanides; Water Oxidation; Electrocatalysis; Photocatalysis; Chemistry